Two new species of Viridantha (Tillandsioideae; Bromeliaceae) - Hernández-Cárdenas, Rodrigo Alejandro; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa (Phytotaxa, 2021)
Viridantha pachycaulis and V. zamudioi, from the states of Jalisco and Querétaro, Mexico, respectively, are described and illustrated as new to science. The proposed taxa are compared to V. mauryana and V. yagulensis, species with which they have some similarities. Morphological descriptions, images and a distribution map of the described taxa are included.